2009
DOI: 10.1002/jbm.b.31385
|View full text |Cite
|
Sign up to set email alerts
|

A study on the influence of biocompatible composites with bioactive ligands toward their effect on cell adhesion and growth for the application in bone tissue engineering

Abstract: The aim of this study was the transformation of the macroporous zirconium dioxide ceramic Sponceram into a biomimetic composite material. To enhance the adhesion of cells and to induce their differentiation into osteoblasts poly-L-lysine and BMP-2 were coupled to polymers and copolymers based on 2-deoxy-N-methacrylamido-D-glucose (ox.p(MAG) and p(MVA)) used as spacer, which were adsorbed onto the ceramic surface. The development of the composite materials was validated step by step qualitatively and quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In this regard, oligo- and polylysines and so-called RGD-peptides are of interest. The first type of molecules are known to enhance the electrostatic adhesion of cells to the surface of materials, while the second ones are responsible for specific cell adhesion via interaction with cells transmembrane receptors-integrins [22,45]. In order to obtain macroporous materials, which are able to attract the cells to their surface, the PLA and PCL matrices were modified by ox-PMAG according to the previously described strategy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, oligo- and polylysines and so-called RGD-peptides are of interest. The first type of molecules are known to enhance the electrostatic adhesion of cells to the surface of materials, while the second ones are responsible for specific cell adhesion via interaction with cells transmembrane receptors-integrins [22,45]. In order to obtain macroporous materials, which are able to attract the cells to their surface, the PLA and PCL matrices were modified by ox-PMAG according to the previously described strategy.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies we suggested the application of the oxidized poly(2-deoxy- N -methacryloylamido- d -glucose) (ox-PMAG) with reactive aldehyde groups to functionalize the bioceramic (Sponceram ® ) surface [43,44]. The results obtained clearly showed that the application of polyvinylsaccharides allowed for controllable attachment of several bioligands, which provided the synergetic effect and induced cell adhesion, differentiation and tissue formation [45]. In this case, the chosen macromolecular spacer, being highly biocompatible and biosimilar, as well bearing the active bioligands, played the role of some vector defining cells behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Once the RGD sequence is recognized by the integrins, it will initiate an integrin-mediated cell attach-ment pathway and activate signal transduction between the cell and ECM, thus influencing various cell behaviors on the substrate including proliferation, differentiation, survival and migration [38]. Roeker et al showed that the composite materials modified by immobilizing poly-L-lysine and BMP-2 as bioactive ligands on the ceramic surface had promising potential to enhance the adhesion of hMSCs and directing cell differentiation into osteoblasts [39]. In another study, it was demonstrated that hMSCs encapsulated in poly (ethylene glycol) (PEG)/ RGD hydrogels undergo chondrogenic differentiation in the presence of TGF-β3.…”
Section: Chemical and Biochemical Cuesmentioning
confidence: 99%
“…4 Cells sense the properties of their environment and continuously adapt their response. [5][6][7][8][9] For example, chondrocytes which are naturally in a high elastic modulus environment hardly adhere to substrates presenting a low elastic modulus. 10,11 However, when the anchoring surface is covered by macromolecular chains, it is not the Young modulus of the material that is the dominant parameter in cell adhesion but rather the response of chain segments over short distances.…”
Section: Introductionmentioning
confidence: 99%